1985
DOI: 10.1021/ma00146a034
|View full text |Cite
|
Sign up to set email alerts
|

Rheooptical response of rodlike chains subject to transient shear flow. 2. Two-color flow birefringence measurements on collagen protein

Abstract: NSF-CPE80-25833) and from the ARCO Foundation. In addition, we thank Professor G. Marrucci for his helpful discussion and the preprint of his paper.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
2

Year Published

1986
1986
2019
2019

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 10 publications
2
44
2
Order By: Relevance
“…shows the β parameter in eq 1 as a function of the nanofibre surface charges, obtained by comparing the length distribution with the contributions B 0 (L) inFigure 2.The β parameters found here are in the range 100 − 1000, i.e. slightly lower than the values reported by other experiments 19,24,25,34. They show a decreasing trend when the surface β parameter as a function of the surface charges of the different nanofibre samples.…”
contrasting
confidence: 52%
See 3 more Smart Citations
“…shows the β parameter in eq 1 as a function of the nanofibre surface charges, obtained by comparing the length distribution with the contributions B 0 (L) inFigure 2.The β parameters found here are in the range 100 − 1000, i.e. slightly lower than the values reported by other experiments 19,24,25,34. They show a decreasing trend when the surface β parameter as a function of the surface charges of the different nanofibre samples.…”
contrasting
confidence: 52%
“…Here β is a numerical factor, k B the Boltzmann constant, T the temperature, L * the entanglement length (see Supporting Information) and η the solvent viscosity. β has been predicted to be of order 1 − 10 24,25,34,36,37 but its magnitude has been found in the range of 10 3 − 10 4 by several experiments 25,26,34,36 and refined theories. 24,37 Results and discussion…”
Section: Inverse Laplace Transformmentioning
confidence: 99%
See 2 more Smart Citations
“…1). 20 Electron microscopy of this collagen preparation (molecules sprayed from acidic solution) revealed that it was approximately 80% monomeric and 13% dimeric with a very low level of higher aggregates 22,23 . The remaining 7% consisted of shortened fragments, which appeared to be bimodal in size distribution, half being about 1/4 and half about 3/4 the length of the native molecule (Fig.…”
Section: Biochemical Characterizationmentioning
confidence: 88%